Membangun Moralitas Kajian Semantik Kata Khuluq dalam Al-Qur’an - Iskandar, Iskandar (Lajnah Pentashihan Mushaf Al-Qur'an, 2009)
The QurÃ¢â‚¬â„¢an is the main source of the Islamic teachings which has a great interest in particular to produce the correct paradigm for human conduct and act, moral acts which by the QurÃ¢â‚¬â„¢an are considered to be part ofÃ‚Â Ã¢â‚¬ËœibadahÃ¢â‚¬â„¢ or Ã¢â‚¬Ëœdevotion to GodÃ¢â‚¬â„¢. Therefore, the QurÃ¢â‚¬â„¢an becomes a very important to create a moral order for all the acts of humankind. This writing tries to show some important aspects of Islamic moral being adopted from the QurÃ¢â‚¬â„¢anic guidances which cover moral terminology, source of moral and basic principles of the moral in its attempt to give some contribution for managing the life of humankind.